Answer:
Step-by-step explanation:
2 csc²x-2 csc x-1=0
or
![\frac{2}{sin^2x} -\frac{2}{sin x} -1=0\\multiply~by~sin^2x\\2-2sin~x-sin^2x=0\\sin^2x+2sinx-2=0\\sin ~x=\frac{-2 \pm\sqrt{2^2-4*1*(-2)} }{2*1} \\=\frac{-2 \pm\sqrt{4+8} }{2} \\=\frac{-2 \pm\sqrt{4*3} }{2} \\=\frac{-2 \pm2\sqrt{3} }{2} \\=-1\pm\sqrt{3} \\|sin~x| \le ~1\\so~sin~x=-1+\sqrt{3} \\sin~x=\sqrt{3} -1\\x=sin^{-1}(\sqrt{3} -1) \approx 47.06^\circ,180-47.06\\or~x=47.06^\circ,132.94^\circ](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bsin%5E2x%7D%20-%5Cfrac%7B2%7D%7Bsin%20x%7D%20-1%3D0%5C%5Cmultiply~by~sin%5E2x%5C%5C2-2sin~x-sin%5E2x%3D0%5C%5Csin%5E2x%2B2sinx-2%3D0%5C%5Csin%20~x%3D%5Cfrac%7B-2%20%5Cpm%5Csqrt%7B2%5E2-4%2A1%2A%28-2%29%7D%20%7D%7B2%2A1%7D%20%5C%5C%3D%5Cfrac%7B-2%20%5Cpm%5Csqrt%7B4%2B8%7D%20%7D%7B2%7D%20%5C%5C%3D%5Cfrac%7B-2%20%5Cpm%5Csqrt%7B4%2A3%7D%20%7D%7B2%7D%20%5C%5C%3D%5Cfrac%7B-2%20%5Cpm2%5Csqrt%7B3%7D%20%7D%7B2%7D%20%5C%5C%3D-1%5Cpm%5Csqrt%7B3%7D%20%5C%5C%7Csin~x%7C%20%5Cle%20~1%5C%5Cso~sin~x%3D-1%2B%5Csqrt%7B3%7D%20%5C%5Csin~x%3D%5Csqrt%7B3%7D%20-1%5C%5Cx%3Dsin%5E%7B-1%7D%28%5Csqrt%7B3%7D%20-1%29%20%5Capprox%2047.06%5E%5Ccirc%2C180-47.06%5C%5Cor~x%3D47.06%5E%5Ccirc%2C132.94%5E%5Ccirc)
Total marbles = 5 + 3 + 2 = 10
Total yellow marbles = 2
P(yellow) = 2/10 = 1/5
Answer: 1/5
Answer:
51.70
Step-by-step explanation:
Answer:
Step-by-step explanation:-16x^2 + 24x + 16 = 0.
A. Divide by 8:
-2x^2 + 3x + 2 = 0, A*C = -2*2 = -4 = -1 * 4. Sum = -1 + 4 = 3 = B, -2x^2 + (-x+4x) + 2 = 0,
(-2x^2-x) + (4x+2) = 0,
-x(2x+1) + 2(2x+1) = 0,
(2x+1)(-x+2) = 0, 2x+1 = 0, X = -1/2. -x+2 = 0, X = 2.
X-intercepts: (-1/2,0), (2,0).
B. Since the coefficient of x^2 is negative, the parabola opens downward. Therefore, the vertex is a maximum.
Locate the vertex: h = Xv = -B/2A = -24/-32 = 3/4, Plug 3/4 into the given Eq to find k(Yv). K = -16(3/4)^2 + 16(3/4) + 16 = 19. V(h,k) = V(3/4,19).
C. Choose 3 points above and below the vertex for graphing. Include the points calculated in part A which shows where the graph crosses the x-axis.
1. 5x + 6 = 2 + 3x
-3x. - 3x
-------------------------
2x + 6 = 2
- 6. - 6
-------------------------
2x = -4
---- -----
2. 2
x = -2
2. 2(6 -2y) = -1(4y-9)
12 -4y = -4y + 9
+4y. +4y
----------------------------
.12 /=\ 9
No solution
3. 2z-6 = 2(z+2) + 10
2z -6 = 2z + 4 + 10
2z -6 = 2z +14
-2z. -2z
-6 /=\ 14
No solution.